2018
DOI: 10.4314/bajopas.v10i1.6s
|View full text |Cite
|
Sign up to set email alerts
|

Studies on <i>in vitro</i> evaluation of antidiabetic potentials of watermellon and pomegranate peels

Abstract: Diabetes is a metabolic disorder which results due to deficiency in insulin and its metabolism. At present, the prevalence of Diabetes has increased worldwide and predicted to increase to greater extent in future generations. Among various therapeutic approaches implemented to prevent diabetes is to regulate the blood glucose levels by various mechanisms. This is being assessed by in vitro antidiabetic assays such as inhibition of carbohydrate digesting enzymes and non-enzymatic glycosylation of haemoglobin. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Methanol extracts of pomegranate peel inhibit glycosylation of hemoglobin for exerting their antidiabetic effect (Sani & Nair, 2017).…”
Section: Antihyperglycemic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Methanol extracts of pomegranate peel inhibit glycosylation of hemoglobin for exerting their antidiabetic effect (Sani & Nair, 2017).…”
Section: Antihyperglycemic Activitymentioning
confidence: 99%
“…Pomegranate peel‐derived punicalagin interacts with α‐glucosidase, thus delaying its role in carbohydrate metabolism (Liu et al., 2022 ). Methanol extracts of pomegranate peel inhibit glycosylation of hemoglobin for exerting their antidiabetic effect (Sani & Nair, 2017 ). Studies have shown that pomegranate peel extract‐stabilized gold nanoparticles significantly decreased the risk of diabetes nephropathy by reducing glucose fasting levels, renal toxicity indices, and serum total cholesterol and triglycerides in a hyperglycemic condition.…”
Section: Health Benefitsmentioning
confidence: 99%
“…Punica granatum, commonly known as the pomegranate, is a plant with a rich history of traditional medicinal uses. Research has shown that P. granatum exhibits a wide range of pharmacological properties and health benefits, highlighting its therapeutic effects in various conditions such as diabetes, cardiovascular diseases, cancer, inflammation, and gastrointestinal issues [9][10][11][12][13]. It was stated that extracts of various parts of P. granatum have an important role in reducing osteoporosis, as well as a gastro-protective effect through the inhibition of gastric mucosal injury [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The vegetables were chosen on the basis of popularity. 7,8 Antidiabetic active compounds such as 1-4, (E)-5-hydroxy-7methoxy-3-(2'-hydroxybenzyl)-4-chromanone, cytopiloyne, stearic acid ethyl ester, 3-beta-D-glucopyranosyloxy-1-hydroxy-6(E)tetradecene-8,10,1 2-triyne, 2-beta-D-glucopyranosyloxy-1-hydroxy-5(E)-tridecene-7,9,11-triyne, 3-beta-D-glucopyranosyloxy-1hydroxy-6(E)-tetradecene-8,10,12-triyn, methyl 4-O-caffeoyl-2-Cmethyl-D-erythronate, 4-O-methylokanin, -(14E, 18E, 22E, 26E) -methyl nonacosa-14, 18, 22, 26 tetraenoate, indole-3-acetonitrile, 4-methoxyindole-3-acetonitrile, indole-3-aldehyde, flavonoids, liquiritin, licochalcone A, sinapic acid, caffeic acid, 2-phenylethyl β-glucopyranoside, salidroside, syringic acid, adenosine, (3β, 20E)ergosta-5, 20 (22)-dien-3-ol, Licochalcone A, caffeic acid, palmitic acid, pheophorbide A-methyl ester and α-spinasterol were isolated from some of the wild plants. Given the large number of in vivo studies, it could be expected that more compounds would have been isolated and tested.…”
Section: Introductionmentioning
confidence: 99%